Cardiogenic shock due to acute coronary syndrome: characteristics and outcomes. (26th April 2021) - Viegas, JM; Grazina, A; Goncalves, AV; Rosa, SA; Ferreira, L; Ferreira, RC
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction:  Among patients admitted to a catheterization laboratory with acute coronary syndrome (ACS), a minority present with cardiogenic shock (CS). Evidence for the best way to manage these patients are needed. Aims:  We aimed to assess patients' characteristics and short and long-term outcomes of ACS presenting with CS. Methods:  We analysed all ACS cases with CS admitted during a ten-year period in a tertiary care centre. We defined CS as systolic blood pressure <90mmHg and signs of impaired organ perfusion with need for catecholamine therapy or presenting with cardiac arrest. At discharge, a standardized registry was performed in all cases, including clinical, electrocardiographic, echocardiographic and angiographic characteristics, and percutaneous coronary intervention (PCI) results. All patients were followed-up for two years for the occurrence of mortality (total and cardiovascular (CV)), CV hospitalizations and revascularization procedures. Results:  From 3283 patients admitted with ACS, 92 (2.8%) presented with CS. Mean age was 66.0 ± 12.8 years, with 64 (69.6%) males, and 60 (65.2%) presenting with ST-segment elevation myocardial infarction. These patients presented previous ACS in 12.0%, were smokers in 28.3% and had diabetes, dyslipidemia and hypertension in 23.9%, 37.0% and 45.7%, respectively. Angiographic characteristics are described in the table. Index-PCI was successful in 83.7% cases. Multivessel coronary artery disease (CAD) was presented in 56 patients (60.9%), of which 20 (21.7%) had 3-vessel disease. Of these 56 patients, complete revascularization in the index-procedure was attempted in 11 patients (19.6%), 10 of which successfully. Mean hospitalization duration of 16.4 ± 9.5 days with in-hospital mortality of 50.0%. Unsuccessful index-PCI (p = 0.002), culprit left main coronary artery (LCMA) (p = 0.044) and reduced left ventricular ejection fraction (LVEF) (p < 0, 001) were significant in-hospital mortality predictors. At 12 and 24 months, survival after hospital release was 95.7% and 91.3%, respectively. At 24 months of follow-up, 40.0% had at least one CV hospitalization, 17.4% being related to a revascularization procedure (PCI 13.0%, coronary artery bypass surgery 4.4%). Conclusion:  CS was uncommon among ACS patients. Unsuccessful PCI, culprit LMCA and reduced LVEF were independent predictors of in-hospital mortality. Despite a very high in-hospital mortality, long-term outcome was favourable.